Developmental Trajectories in Primary Schoolchildren Using n-Back Task - López-Vicente, Mónica; Forns, Joan; Suades-González, Elisabet; Esnaola, Mikel; García-Esteban, Raquel; Álvarez-Pedrerol, Mar; Júlvez, Jordi; Burgaleta, Miguel; Sebastián-Gallés, Núria; Sunyer, Jordi (Frontiers in Psychology, 2016)
Background: Neuropsychological instruments to assess cognitive trajectories during childhood in epidemiological studies are needed. This would improve neurodevelopment characterization in order to identify its potential determinants. We aimed to study whether repeated measures of n-back, a working memory task, detect developmental trajectories in schoolchildren during a one-year follow-up. Methods: We administered the n-back task to 2,897 healthy children aged 7-11 years old from 39 schools in Barcelona (Spain). The task consisted of 2 levels of complexity or loads (2- and 3-back) and 2 different stimuli (numbers and words). Participants performed the task four times from January 2012 to March 2013. To study the trajectories during the follow-up, we performed linear mixed-effects models including school, individual and age as random effects. Results: We observed improvements related to age in n-back outcomes d’, HRT and accuracy, as well as reduced cognitive growth at older ages in d’ and HRT. Greater improvements in performance were observed at younger ages, in 2-back, in verbal rather than numerical stimuli and in girls compared to boys. Boys responded faster at baseline, while girls showed increased growth in 2-back numbers. Children with ADHD (Attention Deficit and Hyperactivity Disorder) symptoms (15% of boys and 6% of girls) had a lower working memory at baseline, but they showed similar cognitive growth trajectories in numbers variants of the task, as compared to children without ADHD symptoms. However, the age-related improvement in response speed was not observed in children with ADHD symptoms. Conclusions: Changes in n-back outcomes reflected developmental trajectories in one-year follow-up. The present results suggest that the repeated administration of this task can be used to study the factors that may alter the cognitive development during childhood.